Aplicação dos processos foto-Fenton e eletrofloculação no tratamento de efluente de curtume - Borba, Fernando Henrique (2010)
Pollution is a currently environmental problem of world concern. There are many events such as the discharging of untreated effluents in watercourses that cause the eutrophization of water bodies and bad water quality, as well as an inefficiency or lack of a current environmental law. The main goal of this dissertation was the application of solar and artificial-based photo-Fenton processes and aluminum electrodes-based electrocoagulation method in non coupled mode and in an integrated mode for the tannery effluent treatment. These effluent treatments were carried out in lab-scale reactors. In order to evaluate the performance of the reactor experimental conditions of photo-Fenton reactor, a 33 complete experimental design was performed. The lab scale EC reactor was operated at the 4 A electrical current, 4 cm electrode distance and 3 initial pH optimized values, according to the previous results obtained in another work, while the electrolysis time was varied from 5 to 120 min. For EC and photo-Fenton reactors, their performance was evaluated on the removal values of chemical oxygem demand (COD), color, turbidity, total solids (TS), total fixed solids (TFS), total volatile solids (TVS) and metal concentration. Measurements of physico-chemical parameters for untreated and treated effluent samples were performed applying the Standard Method for water analysis, while metal concentrations were determined by the Synchrotron radiation total Reflexion X-ray Fluorescence technique at Brazilian Light Synchrotron Laboratory. By an optimized photon-Fenton process at 0.5 g Fe2+ L-1, 30 g H2O2 L-1, 3 initial pH, and 120 min reaction time, tannery effluent was treated achieving a high performance in pollutant removal as reported by 98.1, 96.4, 98.8, 71.8, 32.1 and 98.5 percent removal for COD, color, turbidity, TS, TFS, and TVS, respectively. As a primer treatment stage, electrocoagulation technique was not achieved a well successful result based on the physico-chemical parameter values reduction as compared with photo-Fenton process. However, an integrated solar irradiation-based photo-Fenton and Al electrodes-based electrocoagulation with 15 min electrolysis time has achieved recommended values by the Brazilian environmental law for Cr concentration (0.24 mg Cr L-1) and DQO (107 mg O2 L-1). Considering both the costs of electrical energy and material and the generated sludge discharging, one m3 of tannery effluent should cost R$ 56.30 for a treatment system based on an integrated and optimized photo Fenton and electrocoagulation processes. Finally, the integrated solar-based photo Fenton and electrocoagulation method is suggested as an efficient one, instead to apply a unique process.